Project scope management : a practical guide to requirements for engineering, product, construction, IT and enterprise projects - Moustafaev, Jamal (Boca Raton, Florida : CRC Press, 2015)
Incomplete or missed requirements, omissions, ambiguous product features, lack of user involvement, unrealistic customer expectations, and the proverbial scope creep can result in cost overruns, missed deadlines, poor product quality, and can very well ruin a project. Project Scope Management: A Practical Guide to Requirements for Engineering, Product, Construction, IT and Enterprise Projects describes how to elicit, document, and manage requirements to control project scope creep. It also explains how to manage project stakeholders to minimize the risk of an ever-growing list of user requirements.
Chapter 1. Introduction to scope management : who? -- Chapter 2. History of scope management -- Chapter 3. Writing project charters -- Chapter 4. Requirements, customers, users -- Chapter 5. High-level scope elicitation -- Chapter 6. Detailed requirements elicitation -- Chapter 7. Documenting requirements : information technology and software development projects -- Chapter 8. Documenting requirements: engineering and product development projects -- Chapter 9. Documenting requirements: Multidisciplinary projects -- Chapter 10. Creating the requirements management plan and requirements traceability matrix -- Chapter 11. Final product design -- Chapter 12. Creating work breakdown structures and WBS dictionaries -- Chapter 13. Troubleshooting scope problems -- Chapter 14. Scope verification -- Chapter 15. Controlling project scope.
Includes bibliographical references and index.
Keywords: PLANNING